Case Report: Diagnosis and Management of Long-Standing Essential Hypertension on a Teenager - Miguel Moreta (University Library System, University of Pittsburgh, 2022)
Background: Hypertension affects about one third of the worldwide adult population, in patients aged 18 to 39, prevalence of hypertension is 7.3%. The risk factors for primary hypertension in young adults are the same as in older adults, which include family history of hypertension, poor diet with excess intake of sodium, lack of physical activity, obesity and excess intake of alcohol or tobacco smoking. The treatment of choice for essential hypertension in young adult are lifestyle changes but there is no consensus on the role pharmacological treatment in young hypertensives.   The Case: A 19-year-old patient present with a worsening five-year history of palpitations felt in the abdominal region, tachycardia and high blood pressure. He had a body mass index of 31.3 kg/m2, suboptimal diet and level of physical activity (though he was previously very active) and a family history of essential hypertension. Possible secondary causes of hypertension were ruled out and a diagnosis of essential hypertension was reached through 24-hour ambulatory blood pressure monitoring. The patient was treated with a combination of 5mg amlodipine and 5mg bisoprolol per day as well as lifestyle changes.   Conclusion: This case highlights the increasingly young age of presentation of essential hypertension, especially since the patient refers presence of symptoms as early as 14 years old when he had a relative lack of risk factors. It is important to rule out other potential causes of hypertension in young adults before making a diagnosis of essential hypertension.